The Implementation of the CHA-Q Meta-Model: A Comprehensive, Change-Centric Software Representation - De Roover, Coen; Scholliers, Christophe; Jonckers, Viviane; Pérez, Javier; Murgia, Alessandro; Demeyer, Serge (Electronic Communications of the EASST, 2014)
Although contemporary software development processes have embraced the need for continuous change, most development tools still assume that they act upon a single complete release of the system. The CHA-Q project (Change-centric Quality Assurance) aims to strike a balance between agility and reliability through change-centric quality assurance tools. These tools are to share a first-class representation of changes to software artefacts. In this paper we present the CHA-Q meta-model that defines this representation and highlight important characteristics of its implementation: an object-oriented API, persistency through a graph database, and a strategy for tracking the history of artefacts in a memory-efficient manner.